A review on attitude assessment instruments designed for people who stutter - Seyed Abolfazl Tohidast; Banafsheh Mansouri; Shohreh Jalaei; Seyede Mehri Daryabari (Vesnu Publications, 2013)
Introduction: Stuttering is a communication disorder which includes primary and secondary behaviors. For the assessment, diagnosis and appropriate treatment of stuttering, these two kinds of behaviors should be given sufficient attention. A potential problem in generalizing and maintaining the treatment goals in people who stutter is inappropriate attitudes that may have been prevailed over them through the long periods of experiencing stuttering. For this reason, identifying these attitudes and trying to change them has a major role in the treatment of stuttering. The purpose of this study was to introduce tests to assess the attitude of people with stuttering. Materials and Methods: For a complete and comprehensive access to the attitude assessment instruments in people with stuttering, searching was performed in different databases, books and thesis that were in accordance with the objects of this study. In the next stage, after reviewing the tests, those features that were necessary for the introduction of each test to readers were determined. Results: After reviewing the results, 22 tests were found in the field of assessing attitudes in people with stuttering. Ten tests were related to assessing the attitudes of children, and remaining was related to assessing adults in this regard. These tests are listed in separated tables for more convenient comparisons. Some tests had significant characteristics that will be described. Conclusion: According to the results of the present paper, it can be stated that attitude assessment is an important step in the treatment process of stuttering. This issue needs to be more attended to by speech and language pathologists. Keywords: Stuttering, Assessment, Attitude